Utilizing hydroglycolic extract from myrobalan fruits to counteract reactive oxygen species - Malyn Chulasiri (2018)
Synopsis The hydroglycolic (HG) extract from 70% propylene glycol (PG) extraction of myrobalan fruits showed the most appreciable antioxidant efficiency towards 1,1-diphenyl-2-picrylhydrazyl (DPPH) in comparison to the extracts from 30, 50, 70 and 100% ethyl alcohol (EA), and 30, 50 and 100% PG. Its total polyphenols were also higher than others. The additional analysis of antioxidant power revealed that this HG extract was able to counteract the induced oxidation caused by hydrogen peroxide (H2O2) and 2,2′-azobis(2-amidinopropane) dihydrochloride (AAPH). The quantification for the antioxidant capacity of the extract showed it was equivalent to 93.78 mg of 6-hydroxy-2,5,7,8-tetramethychroman-2-carboxylic acid (Trolox) g -1 by 2,2′-azino-bis(3-ethylbenzthiazoline-6-suphonic acid) diammonium (ABTS) assay, and was 140.17 mg ascorbic acid (AA) equivalent g -1 and 107.50 mg Trolox equivalent g-1 by photochemiluminescence (PCL) assay. The incorporation of the HG myrobalan extract into lotion and sunscreen lotion rendered these products to provide the similar antioxidant power as the extract alone. ICS © 2011 Society of Cosmetic Scientists and the Société Française de Cosmétologie.